An Ethnographic Perspective of the Chautauqua Institution - Allie Brown (Adult Education Research Conference, 2010)
This paper discusses a year long study of the Chautauqua Institution. I used a variety of learning methods in order to gain a better understanding of this uniquely American phenomenon. I conducted telephone interviews with staff, frequently visited the official website and reviewed literature. A week long stay at the Chautauqua Institution during the summer season, afforded me the opportunity to experience the educational offerings and interview other participants and staff. Findings from this cultural immersion experience are discussed in this paper. Implications for future study of the Chautauqua Institution are suggested. Additionally, suggestions for other adult learners desiring to embark on a path of independent learning using an ethnographic approach is included